Bahan Ajar Teks Prosedur Berorientasi Kebudayaan Lokal (Local Culture Oriented Procedure Text Teaching Materials) - Jaja Jaja; Sri Rahayu; Tri Pujiatna (Indonesian Language Education and Literature, 2021)
This study aims to produce handouts oriented to local culture. This development research was conducted from November 2018 to January 2019 in Cirebon Regency. Data were collected through analysis of the structure and linguistic rules of procedure texts in the Indonesian Recipes book. The results of the analysis are used as material to design teaching materials for procedural text handouts. The data is processed descriptively qualitatively and quantitatively to produce handout products suitable for use. Validity is carried out through expert judgment. The results of the study concluded that: the structure of the procedure text that was analyzed was complete and represented using typical linguistic rules, the design was valid, and fit for use. This book can improve students' understanding of procedural texts.Penelitian ini bertujuan menghasilkan handout berorientasi kebudayaan lokal. Penelitian pengembangan ini dilakukan November 2018 sampai Januari 2019 di Kabupaten Cirebon. Data dikumpulkan melalui analisis terhadap struktur dan kaidah kebahasaan teks prosedur dalam buku Resep Masakan Indonesia. Hasil analisis digunakan sebagai bahan untuk merancang bahan ajar handout teks prosedur. Data diolah secara deskriptif kualitatif dan kuantitatif guna menghasilkan produk handout layak pakai. Keabsahan dilakukan melalui penilaian pakar. Hasil penelitian menyimpulkan bahwa: struktur teks prosedur yang dianalisis lengkap dan direpresentasikan dengan menggunakan kaidah kebahasaan yang khas, rancangan valid; dan layak pakai. Buku ini dapat meningkatkan pemahaman siswa terkait teks prosedur.